Disease Burden of Patients With Osteoarthritis: Results of a Cross‐Sectional Survey Linked to Claims Data. Issue 2 (29th January 2020) - Callhoff, Johanna; Albrecht, Katinka; Redeker, Imke; Lange, Toni; Goronzy, Jens; Günther, Klaus‐Peter; Zink, Angela; Schmitt, Jochen; Saam, Joachim; Postler, Anne
Abstract : Objective: Osteoarthritis (OA) is a major reason for chronic pain, stiffness, and functional limitation. This study was undertaken to analyze factors associated with the burden of OA, taking the pattern of joint involvement into account. Methods: From a random sample of 8, 995 patients with OA (International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, German Modification codes M15 [polyarticular], M16 [hip], or M17 [knee]) from a German statutory health insurance database, 3, 564 patients completed a survey including the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Patients with knee, hip, concomitant hip and knee, or polyarticular manifestation were compared concerning pain, stiffness, function, and impact on work and personal life. Data were linked to dispensation records. The association of age, sex, body mass index (BMI), symptom duration, and the World Health Organization–5 Well‐Being Index (WHO‐5) with WOMAC results was assessed in multiple linear regression models. Results: Patients with knee (n = 1, 448), hip (n = 959), hip and knee (n = 399), or polyarthritic (n = 758) OA were included. Concomitant hip and knee OA was accompanied by the highest WOMAC values (mean 44), frequent impairment of personal life (75%), and the highest use of analgesics (52% nonsteroidal antiinflammatory drugs, 22% opioids, and 37% others). In the regression analyses, BMI per 5 units and WHO‐5 per 10% worsening were associated with an increase in WOMAC values of 4–5 points, irrespective of the joint manifestations. Conclusion: Disease burden is high in patients with concomitant hip and knee OA and is connected with frequent prescription of analgesics. Involvement of several joints, BMI, and depressive symptoms need to be considered when using the WOMAC as an outcome instrument.